Pregunta
upstudy study bank question image url

For \( f(x)=\frac{6}{x-5} \) and \( g(x)=\frac{7}{x} \), find the following composite functions and state the domain of each. \( \begin{array}{llll}\text { (a) } f \circ g & \text { (b) } g \circ f & \text { (c) } f \circ f & \text { (d) } g \circ g\end{array} \) \( \begin{array}{l}\text { (a) }(f \circ g)(x)=\square \\ \text { (Simplify your answer. Use integers or fractions for any numbers in the expression.) }\end{array} \)

Ask by Cole Bates. in the United States
Feb 20,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

(a) \( (f \circ g)(x) = \frac{6x}{7 - 5x} \) with domain \( x \neq 0, \frac{7}{5} \) (b) \( (g \circ f)(x) = \frac{7x - 35}{6} \) with domain \( x \neq 5 \) (c) \( (f \circ f)(x) = \frac{6(x - 5)}{31 - 5x} \) with domain \( x \neq 5, 6 \) (d) \( (g \circ g)(x) = x \) with domain \( x \neq 0 \)

Solución

To find the composite functions \( f \circ g \), \( g \circ f \), \( f \circ f \), and \( g \circ g \), we will follow these steps: 1. **Calculate each composite function.** 2. **Determine the domain of each composite function.** ### (a) \( (f \circ g)(x) \) The composite function \( (f \circ g)(x) \) is defined as \( f(g(x)) \). 1. Substitute \( g(x) \) into \( f(x) \): \[ g(x) = \frac{7}{x} \] Therefore, \[ f(g(x)) = f\left(\frac{7}{x}\right) = \frac{6}{\frac{7}{x} - 5} \] 2. Simplify the expression: \[ f\left(\frac{7}{x}\right) = \frac{6}{\frac{7 - 5x}{x}} = \frac{6x}{7 - 5x} \] Thus, \[ (f \circ g)(x) = \frac{6x}{7 - 5x} \] ### Domain of \( f \circ g \) The domain of \( f \circ g \) is determined by the restrictions from both \( g(x) \) and \( f(x) \): - \( g(x) \) is undefined when \( x = 0 \). - \( f(g(x)) \) is undefined when \( g(x) = \frac{7}{x} = 5 \), which gives \( x = \frac{7}{5} \). Thus, the domain of \( f \circ g \) is: \[ \text{Domain: } x \in \mathbb{R} \setminus \{0, \frac{7}{5}\} \] ### (b) \( (g \circ f)(x) \) The composite function \( (g \circ f)(x) \) is defined as \( g(f(x)) \). 1. Substitute \( f(x) \) into \( g(x) \): \[ f(x) = \frac{6}{x - 5} \] Therefore, \[ g(f(x)) = g\left(\frac{6}{x - 5}\right) = \frac{7}{\frac{6}{x - 5}} = \frac{7(x - 5)}{6} \] Thus, \[ (g \circ f)(x) = \frac{7(x - 5)}{6} = \frac{7x - 35}{6} \] ### Domain of \( g \circ f \) The domain of \( g \circ f \) is determined by the restrictions from both \( f(x) \) and \( g(x) \): - \( f(x) \) is undefined when \( x = 5 \). - \( g(f(x)) \) is defined for all \( f(x) \) except when \( f(x) = 0 \), which does not occur since \( f(x) \) is never zero. Thus, the domain of \( g \circ f \) is: \[ \text{Domain: } x \in \mathbb{R} \setminus \{5\} \] ### (c) \( (f \circ f)(x) \) The composite function \( (f \circ f)(x) \) is defined as \( f(f(x)) \). 1. Substitute \( f(x) \) into itself: \[ f(f(x)) = f\left(\frac{6}{x - 5}\right) = \frac{6}{\frac{6}{x - 5} - 5} \] 2. Simplify the expression: \[ f\left(\frac{6}{x - 5}\right) = \frac{6}{\frac{6 - 5(x - 5)}{x - 5}} = \frac{6(x - 5)}{6 - 5x + 25} = \frac{6(x - 5)}{31 - 5x} \] Thus, \[ (f \circ f)(x) = \frac{6(x - 5)}{31 - 5x} \] ### Domain of \( f \circ f \) The domain of \( f \circ f \) is determined by the restrictions from \( f(x) \): - \( f(x) \) is undefined when \( x = 5 \). - \( f(f(x)) \) is undefined when \( f(x) = 5 \), which gives \( x = 6 \). Thus, the domain of \( f \circ f \) is: \[ \text{Domain: } x \in \mathbb{R} \setminus \{5, 6\} \] ### (d) \( (g \circ g)(x) \) The composite function \( (g \circ g)(x) \) is defined as \( g(g(x)) \). 1. Substitute \( g(x) \) into itself: \[ g(g(x)) = g\left(\frac{7}{x}\right) = \frac{7}{\frac{7}{x}} = x \] Thus, \[ (g \circ g)(x) = x \] ### Domain of \( g \circ g \) The domain of \( g \circ g \) is determined by the restrictions from \( g(x) \): - \( g(x) \) is undefined when \( x = 0 \). Thus, the domain of \( g \circ g \) is: \[ \text{Domain: } x \in \mathbb{R} \setminus \{0\} \] ### Summary of Results - \( (f \circ g)(x) = \frac{6x}{7 - 5x} \) with domain \( x \in \mathbb{R} \setminus \{0, \frac{7}{5}\} \) - \( (g \circ f)(x) = \frac{7x - 35}{6} \) with domain \( x \in \mathbb{R} \setminus \{5\} \) - \( (f \circ f)(x) = \frac{6(x - 5)}{31 - 5x} \) with domain \( x \in \mathbb{R} \setminus \{5, 6\} \) - \( (g \circ g)(x) = x \) with domain \( x \in \mathbb{R} \setminus \{0\} \)

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To find the composite functions, let's evaluate each one step by step. ### (a) \( (f \circ g)(x) \) To find \( (f \circ g)(x) \), we need to substitute \( g(x) \) into \( f \): \[ g(x) = \frac{7}{x} \quad \implies \quad f(g(x)) = f\left(\frac{7}{x}\right) = \frac{6}{\frac{7}{x} - 5} \] Let's simplify: \[ = \frac{6x}{7 - 5x} \] **Domain:** We need \( x \neq 0 \) (from \( g(x) \)) and \( 7 - 5x \neq 0 \) leading to \( x \neq \frac{7}{5} \). Thus, the domain is \( x \in \mathbb{R}, x \neq 0, \frac{7}{5} \). ### (b) \( (g \circ f)(x) \) To find \( (g \circ f)(x) \), we substitute \( f(x) \) into \( g \): \[ f(x) = \frac{6}{x - 5} \quad \implies \quad g(f(x)) = g\left(\frac{6}{x - 5}\right) = \frac{7}{\frac{6}{x - 5}} \] Simplifying this gives: \[ = \frac{7(x - 5)}{6} = \frac{7x - 35}{6} \] **Domain:** We need \( x - 5 \neq 0 \) (so \( x \neq 5 \)) and since \( f(x) \) is defined for \( x \neq 5 \), the domain is \( x \in \mathbb{R}, x \neq 5 \). ### (c) \( (f \circ f)(x) \) To find \( (f \circ f)(x) \): \[ f(f(x)) = f\left(\frac{6}{x - 5}\right) = \frac{6}{\frac{6}{x - 5} - 5} \] Simplifying: \[ = \frac{6(x - 5)}{6 - 5(x - 5)} = \frac{6(x - 5)}{35 - 5x} \] **Domain:** We require \( x \neq 5 \) and \( 35 - 5x \neq 0 \) (leading to \( x \neq 7 \)). Thus, the domain is \( x \in \mathbb{R}, x \neq 5, 7 \). ### (d) \( (g \circ g)(x) \) To find \( (g \circ g)(x) \): \[ g(g(x)) = g\left(\frac{7}{x}\right) = \frac{7}{\frac{7}{x}} = x \] **Domain:** Since \( g(x) \) is undefined at \( x = 0 \), the domain is \( x \in \mathbb{R}, x \neq 0 \). In summary: - \( (f \circ g)(x) = \frac{6x}{7 - 5x} \) with domain \( x \in \mathbb{R}, x \neq 0, \frac{7}{5} \) - \( (g \circ f)(x) = \frac{7x - 35}{6} \) with domain \( x \in \mathbb{R}, x \neq 5 \) - \( (f \circ f)(x) = \frac{6(x - 5)}{35 - 5x} \) with domain \( x \in \mathbb{R}, x \neq 5, 7 \) - \( (g \circ g)(x) = x \) with domain \( x \in \mathbb{R}, x \neq 0 \)

preguntas relacionadas

Latest Pre Calculus Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad